HUBUNGAN ANTARA KELINCAHAN DENGAN KEMAMPUAN MENGGIRING BOLA PADA KLUB SEPAK BOLA KARANG TARUNA DESA TABABU KOLAKA TIMUR - saca winata; Woter Mongsidi; muh zaenal arwih (JOKER (Jurnal Ilmu Keolahragaan), 2020)
The purpose of this study was to determine the relationship between agility and the ability to dribble at the youth soccer club, Tababu Kolaka Timur village. The population in this study were all members of the Tababu village youth soccer club, perhaps 30 people. The sample in this study were all members of the population who took 20 people who were taken with a total sampling technique where the entire population was used as the research sample. The instruments used in this study were the Illinois agility test for the agility variable and the dribbling slalom test for the dribbling variable. Based on the results of the data, data processing, and research results obtained and previously stated, it can be denied that agility has a relationship that has the ability to lead to the Tababu village youth soccer club, where rxy = 0.542> r2 table (0.05: 20 ) = 0.29 with a coefficient of determination = R20.29 or 29% of the components of the agility physical ability component contribute to the ability to dribble